The Pros and Cons of English Learning Strategies in the Post Covid-19 Pandemic of Vocational High School: Perception and Attitude by Indonesian EFL Learners - Ana Retnowati; Agus Wijayanto; Mauly Halwat Hikmat (AL-ISHLAH: Jurnal Pendidikan, 2023)
During the outbreak of the Covid-19 pandemic, students and teachers had to carry out academic activities via online learning management system. Recently the threat of Covid-19 has receded and schools immediately carry out full face-to-face learning. The present study observed high school students’ perception of the shifts of English learning from blended to offline learning. The research data was obtained through a questionnaire from 286 students consisting of 118 males and 168 females in Central Java, Indonesia. The results reveal some pros and cons towards offline learning. In general, students accustomed to online learning find offline learning time-consuming and burdensome. However, most of them state that offline learning is fun, more interesting, and more effective. Importantly, they could meet their classmates and teachers in person again. The study concluded that offline learning or traditional classrooms were preferred to online learning.